Implementation of direct torque control of induction machines utilizing Digital Signal Processor (DSP) and Field Programmable Gate Arrays (FPGA) - Toh, Chuen Ling (2005)
This thesis presents the implementation of a high performance Direct Torque Control (DTC) of induction machine (IM) drives. A summary of the theoretical aspects and principles of DTC are given with emphasis on two major problems, i.e. high torque ripple and variable switching frequency. In order to solve these problems, this thesis proposed a pair of torque and flux controllers to replace the hysteresis-based controllers. The proposed torque controller consists of a PI controller, 2 triangular carrier generators and a pair of comparator. It produces three level output, namely â€“1, 0, and 1, which is similar to the three level hysteresis comparator. The proposed flux controller works similar to the torque controller and consists of a proportional controller, a single triangular carrier generator and a comparator. The output is switched between 1 and 0 similar to the two-level hysteresis comparator. The design of these controllers is thoroughly discussed and is applied to a Â¼ HP squirrel cage IM. The simulation of the proposed controllers applied to the DTC drive is presented. The simulation results are then verified by experimental results. The main components of the hardware are implemented using DSP TMS320C31 and Altera FPGA devices. The DSP is used to estimate the torque and flux while the FPGA is responsible in generating the triangular carriers, selecting the appropriate voltage vectors and generating the blanking time for the 3-phase VSI. The results prove that 80% of torque ripple reduction is obtained while the stator flux ripples also manage to achieve 57% of reduction. Furthermore, the switching frequency is fixed at 10.4 kHz and a smoother sinusoidal phase current is obtained.